Control strategy for a CO2-based combined cooling and power generation system based on heat source and cold sink fluctuations. (15th October 2022) - He, Jintao; Shi, Lingfeng; Tian, Hua; Wang, Xuan; Zhang, Yonghao; Zhang, Meiyan; Yao, Yu; Cai, Jinwen; Shu, Gequn
Abstract: The CO2 -based combined cooling and power system (CCP) is considered a promising solution for waste heat recovery due to its environmental protection and excellent performance. When it comes to refrigerated trucks' application, there are still critical challenges arising from the transient fluctuations of cold and heat sources. According to the poor correlation between the power sub-cycle and the refrigeration sub-cycle of the CCP system, this paper proposes various controls such as constant control and optimal control to control each cycle separately and achieve stable and optimized operation. The results show that the optimal pump speed and the split valve to limit exhaust control is an effective strategy for engine heat source fluctuations. Under the engine heat source slow step condition, the net work under this control is improved by 5%, and under the engine heat source transient condition, the net work under this control is only improved by 1.37%. In the case of cold sink fluctuations, the strategy of controlling the condensing pressure can reduce the maximum fluctuation of the cooling capacity from 5% under open-loop conditions to 2.5% under control. The above control methods can make the operation of the CCP system more stable and effective. Highlights: Independent control strategies are formulated to deal with fluctuations in heat source and cold sink respectively. Compare various control strategies to provide basis for strategy selection under different operating conditions. The optimal pump speed control is more suitable for slow step conditions rather than transient conditions.